Perbandingan Luaran Maternal dan Perinatal Kehamilan Terkonfirmasi Covid-19 antara Gelombang Pertama dan Kedua Pandemi - Irsan, Raissa Alifia; Farhanah, Nur; Trisetiyono, Yuli; Cahyanti, Ratnasari Dwi (JURNAL KESEHATAN REPRODUKSI, 2023)
Background : New cases of COVID-19 continued to emerge due to the new variants. Pregnant women are more susceptible to severe infections.Objective : To compare the effect of COVID-19 infection on maternal and perinatal outcomes in the first and second waves.Method : An analytical observational study with a cross-sectional design was used. Samples were selected by consecutive sampling from the medical record data of RSUP Dr. Kariadi Semarang, Indonesia, with 47 cases during the first wave (1 August 2020 to 14 May 2021) and 47 cases during the second wave (16 May to 30 September 2021). Data were analysed using univariate, chi-square, fisher’s exact, and logistic regression tests with a significant value of p <0,05.Results and Discussion : Pneumonia, ICU admission, and oxygen consumptions were higher in the second than the first wave as 87.23% VS 70.21%; p = 0.044, 36.17% VS 14.89%; p = 0.018, 65.96% VS 12.77%; p < 0.0001 respectively. The severe COVID-19 infection and maternal mortality increased in the second wave (51,06% VS 14,89%; p = 0.009; 29,79% VS 8,51%; p = <0.001). There were no differences in perinatal outcomes between the first and second waves such as fetal distress, fetal growth retardation, low birth weight, nICU admission, and mortality (0.00% VS 8.51%; p = 0.117, 0.00% VS 4.26%; p = 0.495, 12.77% VS 25.53%; p = 0.116, 12.77% VS 21.28%; p = 0.272, 4.26% VS 8.51%; p = 0.677). The incidence of COVID-19 infection in neonates remained low in both waves at 17.02% VS 12.77%; p = 0.562.Conclusion : Even though a high number of severe diseases to maternal deaths were found during the second wave, neonatal COVID-19 infections remained low.